Efficacy of Periarticular Infiltration with Dexamethasone and Bupivacaine plus Adductor Canal Block Relative to That of Adductor Canal Block Alone for Patients Undergoing Total Knee Arthroplasty: A Retrospective Case-Matched Study - Varah Yuenyongviwat; Bunyaporn Wuttiworawanit; Nipat Panichnantho; Theerawit Hongnaparak; Khanin Iamthanaporn (Advances in Orthopedics)
Purpose. Periarticular infiltration (PI) is a common procedure during total knee arthroplasty (TKA) for postoperative pain management. This retrospective, case-matched study aimed to evaluate the effectiveness of PI with dexamethasone and bupivacaine in combination with an adductor canal block (ACB) and compare it with that of ACB alone in reducing postoperative pain in patients with TKA. Methods. Data were collected from 66 patients who underwent TKA performed by a single surgeon. Thirty-three of them received ACB + PI, and 33 received ACB alone. However, both groups underwent identical surgical techniques and postoperative care protocols. The pain scores and fentanyl consumption of the two groups were compared. Results. The ACB + PI group had significantly lower pain scores than the ACB alone group at 8, 16, 24, and 48 hours postoperatively (p=0.033, 0.004, 0.038, and 0.049, respectively). The percentage of patients requiring fentanyl as a rescue medication was significantly higher for the ACB alone group (90.9%) than for the ACB + PI group (69.7%, p=0.03). The total fentanyl consumption was also lower for the ACB + PI group (p<0.001). Conclusion. The periarticular injection of the combination of dexamethasone and bupivacaine plus ACB was more effective than ACB alone in reducing postoperative pain and fentanyl consumption in patients undergoing TKA. Further studies comparing different doses of dexamethasone or other cocktail regimens may provide additional insights into this approach.